A critical review on purification methods and applications of marine algal haloperoxidases - Rahim, Abdellatif; Benjamaa, Rania; Essamadi, Abdel Khalid; Chafik, Abdelbasset (Frontiers in Natural Products, 2025)
Marine algae are a rich and underexplored source of haloperoxidases, enzymes with wide ranging applications in biocatalysis, pharmaceuticals, and environmental bioremediation due to their ability to catalyze the halogenation of organic compounds. This review focuses on the recent advancements in the purification of haloperoxidases from marine algae, highlighting both traditional and innovative methods. We discussed the limited exploration of green algal haloperoxidases, and the potential for discovering novel enzymes with unique properties. The review examines the advantages and disadvantages of chromatographic techniques, such as ion-exchange, size exclusion, and affinity chromatography, and explores emerging alternatives, including aqueous two-phase systems (ATPS) and microfluidic systems, for improving enzyme yield, purity, and stability. The use of ATPS to address challenges posed by alginate-rich brown algae is emphasized, along with optimization strategies for scaling up purification processes. The growing importance of sustainable and green chemistry approaches to minimize environmental impact while achieving high purification efficiency is also discussed. By analyzing current purification techniques, identifying knowledge gaps, and suggesting future research directions, this review aims to provide meaningful insights into the purification and industrial applications of haloperoxidases, thereby stimulating further exploration and innovation in this field.